2022
DOI: 10.3390/min12081039
|View full text |Cite
|
Sign up to set email alerts
|

S and Sr Isotope Compositions and Trace Element Compositions of the Middle Jurassic Evaporites in Eastern Tibet: Provenance and Palaeogeographic Implications

Abstract: The origin of Middle Jurassic evaporites in the Qamdo Basin is still controversial because palaeontological studies have reported that they have both marine and continental characteristics. The 87Sr/86Sr ratios of the gypsum in the Middle Jurassic Dongdaqiao Formation in the Qamdo Basin range from 0.707602 to 0.708163, which are higher than that of contemporaneous seawater. Model calculations suggest that continental water prevailed over seawater during the precipitation of these evaporites. However, the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…A large amount of information regarding paleosalinity, initial brine composition, depositional basin water depth, paleotemperature, evaporite origins, and diagenetic processes have been based on the geochemistry of major and trace elements [ [5] , [6] , [7] ]. Moreover, a significant contribution for determining the origin, marine vs non-marine, of ancient evaporites and the influence of different water types on the depositional basin may be acquired from the use of strontium ( 87 Sr/ 86 Sr), oxygen (δ 18 O sulfate ), and sulfur (δ 34 S sulfate ) isotope data [ [8] , [9] , [10] , [11] ]. Karakaya et al [ 9 ] employed 34 S and 18 O values to deduce the contribution of the recycling-dissolution of the predeposited marine sulfates (Oligocene-Eocene), arid conditions and bacterial sulfate reduction processes on the compositions of the Miocene evaporites in the Tuz Gölü basin, Turkey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of information regarding paleosalinity, initial brine composition, depositional basin water depth, paleotemperature, evaporite origins, and diagenetic processes have been based on the geochemistry of major and trace elements [ [5] , [6] , [7] ]. Moreover, a significant contribution for determining the origin, marine vs non-marine, of ancient evaporites and the influence of different water types on the depositional basin may be acquired from the use of strontium ( 87 Sr/ 86 Sr), oxygen (δ 18 O sulfate ), and sulfur (δ 34 S sulfate ) isotope data [ [8] , [9] , [10] , [11] ]. Karakaya et al [ 9 ] employed 34 S and 18 O values to deduce the contribution of the recycling-dissolution of the predeposited marine sulfates (Oligocene-Eocene), arid conditions and bacterial sulfate reduction processes on the compositions of the Miocene evaporites in the Tuz Gölü basin, Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Karakaya et al [ 9 ] employed 34 S and 18 O values to deduce the contribution of the recycling-dissolution of the predeposited marine sulfates (Oligocene-Eocene), arid conditions and bacterial sulfate reduction processes on the compositions of the Miocene evaporites in the Tuz Gölü basin, Turkey. The lithologies and Sr isotope compositions of Middle Jurassic evaporites in the Qamdo and Qiangtang Basins of Eastern Tibet were compared by Fei et al [ 10 ]. Their findings suggested that the Qiangtang Basin was mostly recharged by Jurassic seawater, whereas the Qamdo Basin was primarily recharged by continental water, with some Qiangtang Basin-derived overflow.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur isotopic techniques have been widely used to study evaporites in saline lakes in recent years [5], as they allow for regional and even global comparison of marine sedimentary layers due to their highly regular distribution in sulfate. Especially under complex conditions, analyzing the distribution of sulfur isotopes provides substantial evidence for reconstructing paleogeographic sedimentary environments and understanding the genesis of evaporites [6][7][8][9]. The sulfur isotope composition of marine evaporites records the evolutionary history of seawater sulfates in different geological periods.…”
Section: Introductionmentioning
confidence: 99%